2001
DOI: 10.1046/j.1365-2648.2001.01779.x
|View full text |Cite
|
Sign up to set email alerts
|

Forced externalization of control in people with diabetes: a qualitative exploratory study

Abstract: The findings also suggested that participants in this study might have felt that the control of their chronic condition had been externalized to the health care professionals responsible for their care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 57 publications
(69 reference statements)
2
68
1
1
Order By: Relevance
“…Overall, results indicate that patients experience a wide range of emotions at diagnosis, including shock, anxiety, denial, anger, fear, and loss of control on the one hand, and relief and affirmation on the other (Dietrich, 1996;Gillibrand & Flynn, 2001 report various emotions found that between one-quarter and one-half experience strong negative emotions at diagnosis (Beeney, Bakry, & Dunn, 1996;Lo & Maclean, 2001).…”
Section: Screen-detected Patientsmentioning
confidence: 93%
See 1 more Smart Citation
“…Overall, results indicate that patients experience a wide range of emotions at diagnosis, including shock, anxiety, denial, anger, fear, and loss of control on the one hand, and relief and affirmation on the other (Dietrich, 1996;Gillibrand & Flynn, 2001 report various emotions found that between one-quarter and one-half experience strong negative emotions at diagnosis (Beeney, Bakry, & Dunn, 1996;Lo & Maclean, 2001).…”
Section: Screen-detected Patientsmentioning
confidence: 93%
“…Results of these studies suggest that patients are not so much concerned about the long-term threats to their health but rather focus on the short-term impact of medical treatment and lifestyle changes on their daily lives, diet in particular (Everett & Kerr, 1998;Gillibrand & Flynn, 2001). Furthermore, for many patients having diabetes was synonymous with having to take injections, a topic which many patients were concerned about regardless of whether it was part of their treatment (Beeney et al, 1996;Everett & Kerr, 1998).…”
Section: Worries and Concerns: Contentmentioning
confidence: 98%
“…The literature describing the use of the Multidimensional Health Locus of Control scales with African Americans documents a greater external locus of control among those with diabetes and in the elderly. 22,23,26 Several studies suggest that persons with a high powerful others locus of control might be more adherent to physician or family recommendations for behavior change. 22,26 Most respondents classifi ed themselves as in the maintenance stage of change for regular exercise (46%) or healthy diet behavior (57%).…”
Section: Discussionmentioning
confidence: 99%
“…20 Whereas the health locus of control model has been applied to African American communities in a variety of settings, there are fewer studies of its use in diabetes and cardiovascular disease. [21][22][23][24][25][26] This article provides information about participation in protective health behaviors (physical activity and diet), health locus of control, and stage of readiness to change in an African American community. We discuss how quantitative and qualitative analyses of these data have been used to refi ne existing community-based health promotion interventions in our COPC project.…”
mentioning
confidence: 99%
“…Complex treatments involving both lifestyle change and numerous medications can be very demanding, confronting patients with their disease on a daily basis while simultaneously making them more dependent on the health care system (11,12). As a result, many practitioners may be hesitant to treat patients with newly diagnosed diabetes intensively, despite the potential medical benefits.…”
mentioning
confidence: 99%